2020
DOI: 10.3389/fphy.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

The Case for the Fundamental MBH-σ Relation

Abstract: Strong scaling relations between host galaxy properties (such as stellar mass, bulge mass, luminosity, effective radius etc) and their nuclear supermassive black hole's mass point toward a close co-evolution. In this work, we first review previous efforts supporting the fundamental importance of the relation between supermassive black hole mass and stellar velocity dispersion (M BH-σ e). We then present further original work supporting this claim via analysis of residuals and principal component analysis appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 106 publications
1
23
0
Order By: Relevance
“…Bulge + disc decomposition relies on several aspects/assumptions (each study having its own) and can suffer from lack of information on the inclination, surface brightness limits, spatial resolution, and signal-to-noise ratio (see discussions in Simard et al 2011;Dubois et al 2012;Volonteri et al 2016). It has been shown that the M BH − σ plane could be more fundamental than those with galaxy stellar luminosity or mass, or effective radius (for a review Marsden et al 2020). At relatively low redshift, there is no observational evidence for a redshift evolution of the M BH − σ relation, as demonstrated by Shen et al (2015) using about 90 SDSS quasars at z < 1 and by indirect estimates (Shankar, Bernardi & Haiman 2009a;Zhang, Lu & Yu 2012).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulge + disc decomposition relies on several aspects/assumptions (each study having its own) and can suffer from lack of information on the inclination, surface brightness limits, spatial resolution, and signal-to-noise ratio (see discussions in Simard et al 2011;Dubois et al 2012;Volonteri et al 2016). It has been shown that the M BH − σ plane could be more fundamental than those with galaxy stellar luminosity or mass, or effective radius (for a review Marsden et al 2020). At relatively low redshift, there is no observational evidence for a redshift evolution of the M BH − σ relation, as demonstrated by Shen et al (2015) using about 90 SDSS quasars at z < 1 and by indirect estimates (Shankar, Bernardi & Haiman 2009a;Zhang, Lu & Yu 2012).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…These scaling relations are mostly observed in the local Universe since it is extremely challenging to measure these quantities at higher redshifts. For this reason, we only study the M BH − M relation in this paper (M being easier to measure), even if BH mass scales more tightly with the galaxy velocity dispersion locally (Saglia et al 2016;Shankar et al 2016;de Nicola, Marconi & Longo 2019;Marsden et al 2020). The scaling relations potentially imply the co-evolution of BHs and their host galaxies.…”
mentioning
confidence: 99%
“…Many studies have suggested that the M BH -σ relation may be the most fundamental/universal relation (e.g., Ferrarese & Merritt 2000;Gebhardt et al 2000;Ferrarese & Ford 2005;de Nicola et al 2019;Marsden et al 2020) between a black hole and the host galaxy due to its obvious link with the galaxy's gravitational potential and the appearance of M BH ∝ σ 4−5 relations in theories trying to explain black hole feedback (Silk & Rees 1998;Fabian 1999). These claims are based on past observations (van den Bosch 2016; Saglia et al 2016) which reported a single M BH -σ relation for all galaxy types (including bulge-less galaxies), and also a smaller scatter seen in the M BH -σ diagram relative to the M BH -M * ,sph relation.…”
Section: Fundamental Black Hole Scaling Relationmentioning
confidence: 99%
“…Kormendy & Ho 2013 and references therein) indicate that controlling the morphology of the AGN hosts is essential when studying the evolution of scaling relations with redshift. Besides this, the stellar velocity dispersion (σ ) is the most fundamental parameter linking galaxies and SMBHs (Shankar et al 2016;Marsden et al 2020). Moreover, only the M BH −σ relation holds to all galaxy types, from dwarfs to the most massive galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%